Toward a three-dimensional vision of the different compositions and the stratigraphy of the painting L’Homme blessé by G. Courbet: coupling SEM–EDX and confocal micro-XRF - Reiche, Ina; Müller, Katharina; Mysak, Erin; Eveno, Myriam; Mottin, Bruno (Applied physics. A, Materials science & processing, 2015)
Examination of Gustave Courbet’s L’Homme blessé (Musee d’Orsay, Paris), a painting with three successive compositions on a single canvas, was undertaken with scanning electron microscopy coupled with an energy-dispersive X-ray analyzing system (SEM–EDX) on cross sections taken in the 1970s at the Laboratoire de Recherche de Musées de France, Paris and confocal X-ray fluorescence spectroscopy (CXRF) analysis adjacent to the sample locations of the three previously removed cross sections. Recent developments of in situ techniques such as CXRF have enabled investigation of the chemical composition of complicated paint layering without sampling. Here, we compare depth profiling by CXRF analysis with SEM–EDX data from cross sections with the goal of understanding how well CXRF data represent such a complicated paint stratigraphy. Beyond suggesting the paint palettes for Courbet’s three compositions, this new data provide insight into the complex paint layer stratigraphy of eight or more layers and serve as the basis for interpreting further analyses by scanning XRF and CXRF of additional areas of interest on the painting. Data from these additional locations will be discussed in a forthcoming paper.